2015
DOI: 10.1007/s13277-015-3355-9
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive microRNA-200a inhibits renal cell carcinoma development by directly targeting TGFB2

Abstract: A large body of evidence indicates that microRNAs play a critical role in tumor initiation and progression by negatively regulating oncogenes or tumor suppressor genes. Here, we report that the expression of miR-200a was notably downregulated in 45 renal cell carcinoma (RCC) samples. Restoration of miR-200a suppressed cell proliferation, migration, and invasion in two RCC cell lines. Furthermore, we used an epithelial-to-mesenchymal transition PCR array to explore the putative target genes of miR-200a. By perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
(56 reference statements)
1
19
0
Order By: Relevance
“…The results of the co-transfection experiments using constructs encoding eGFP-3′-UTR of TGFβ2 and DsRed-miR-200a revealed that miR-200a directly bound the 3′-UTR of TGFβ2 and silenced its expression. Our identification of chicken TGFβ2 as a target of gga-miR-200a-3p is consistent with earlier reports in mice and humans [38,39] and, to our knowledge, for the first time, two other genes, MAP2K4 and ZAK, were also identified as the targets of gga-miR-200a-3p in this study. ZAK is a MAPK-kinase kinase (MKKK) which was involved in the activation of the ERK, p38 signaling pathways [40,41].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the co-transfection experiments using constructs encoding eGFP-3′-UTR of TGFβ2 and DsRed-miR-200a revealed that miR-200a directly bound the 3′-UTR of TGFβ2 and silenced its expression. Our identification of chicken TGFβ2 as a target of gga-miR-200a-3p is consistent with earlier reports in mice and humans [38,39] and, to our knowledge, for the first time, two other genes, MAP2K4 and ZAK, were also identified as the targets of gga-miR-200a-3p in this study. ZAK is a MAPK-kinase kinase (MKKK) which was involved in the activation of the ERK, p38 signaling pathways [40,41].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, IL17, as a representative of interleukins, is associated with lung and colorectal cancer progression and predicts poor prognosis in breast cancer [810]. Even though some studies suggested an impact in RCC, the role of cytokines and chemokines in RCC progression is poorly understood [1, 11, 12]. From a clinical point of view, cytokine and chemokine secretion into the blood stream makes them very suitable as noninvasive clinical markers.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, the roles of cellular miRNA abnormalities in the pathogenesis of most human cancers have been intensely investigated. [25][26][27] Furthermore, the miR-200a-3p/ CBL pathway has not been explored in RCC. In the current study, we focused on understanding the pathological roles of miR-200a-3p in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] To further uncover the underlying mechanisms of the suppression of RCC cell growth and migration mediated by miR-200a-3p, we searched for miRNA targets and identified CBL as a novel target of miR-200a-3p. [26][27][28] To further uncover the underlying mechanisms of the suppression of RCC cell growth and migration mediated by miR-200a-3p, we searched for miRNA targets and identified CBL as a novel target of miR-200a-3p.…”
Section: Discussionmentioning
confidence: 99%